A preliminary report on the feasibility of regression-based alignment of diagnostic thresholds for harmonized use of international classification criteria for antiphospholipid syndrome - Yukari Motoki; Risa Kaneshige; Yuichiro Fujieda; Kenji Oku; Eriko Morishita; Masahiro Ieko; Tatsuya Atsumi; Kiyoshi Ichihara; Junzo Nojima (PLoS ONE, 2025)
Background In 2023, international rheumatology societies issued new classification criteria for antiphospholipid syndrome (APS). The criteria require scoring antiphospholipid antibody (aPL) titers as moderate or high using the traditional thresholds of 40U or 80U determined by “standardized” ELISA. With current popularity of non-standardized aPL assays (non-ELISA), we aimed to broaden the application of the criteria by estimating equivalent thresholds for them. Methods Four types of aPLs (aCL/aβ2GPI-IgG/IgM) were measured using six reagents in 50 APS and 50 non-APS patients. By regression analysis of measurements between standardized ELISA and non-ELISA assays, thresholds equivalent to 10, 20, 40 and 80U were estimated for each assay. Data points below the detection limit of each assay were excluded from the regression. The diagnostic thresholds were also evaluated using “specificity-based” method described by the International Society on Thrombosis and Haemostasis (ISTH). This approach allegedly estimates diagnostic thresholds that attain predefined specificities of 0.975 and 0.995 in distinguishing APS from non-APS cases, respectively corresponding to moderate and high titers. The between-assay concordance of diagnostic classification using the estimated thresholds was calculated as kappa coefficient (κ). Results Using major-axis regression, thresholds equivalent to the traditional units (10 − 80U) were estimated for non-ELISA assays, which led to harmonized semi-quantitative classification with high κ values. Conversely, the specificity-based method yielded thresholds that dissociated from the traditional ones, particularly for IgG-isotype assays, resulting in lower κ values than regression-based method (P = 0.0039 − 0.0098). Conclusion The regression-based conversion of diagnostic thresholds is practical in harmonizing diagnostic classification across major aPL assays. The specificity-based method may need adjusted predefined-specificities to estimate thresholds that are equivalent to the traditional thresholds.